DESAIN INTERIOR KARATON KASUNANAN SURAKARTA PASCA KEBAKARAN TAHUN 1985 (STUDI KASUS INTERIOR SASANA HANDRAWINA) - Agung Purnomo (SURYA SENI, 2008)
Interior Design of Karaton Kasunanan Surakarta, Post Conﬂ agration in 1985: Case Study of Sasana Handrawina’s Interior. Sasana Handrawina in Kedaton Karaton Kasunanan Surakarta has a function as a place for banquet foe royal guest and royal families. The existence of Sasana Handrawina is signiﬁcant and being one unity with anoyher building suchas Sasana Prasadya and Dalem Prabasuyasa. Built in 1745 by Pakubuwana V, this beautiful interior building had experienced conﬂ agration in 1985. The purpoe of this research is to know what the planningnconcet in Sasana Handrawina Interior’s reconstrusction as a place for banquet or royal dinner,involving, function, activities, room organization, element shaper of the room, aesthetic element, and condition order of the room. Beside, the purpose is also to know how the change of Sasaa Handrawina interior after being rebuilt and whatfactors forcing the change. Design approach needs to be done because the object of the research belongs tothe ﬁ eld of interior design, where thr element inside of it needs tobe seen from the approach. While sosiohistoric approach deals with Sasana Handrawina interior is realized at present.Changes happening to interior design elements of Sasana Handrawina are caused by several factors both internal and external. Revitalization as development concept of Karaton  now to the future is an important element in controlingchange boundaries, which are still allowed. It is so relevant with the existence of Karaton as one running monument, which is one side must reserved as the  sites in it considered important. While on the other side, Karaton is not only  artifact but also the beat of cultural life growing and expanding continuosly in accordance with the change of era.Keywords: interior, reconstruction, and change